Isti’żān as a Mechanism for Protecting Privacy and Individual Honor in the Tafsir of Mafātīḥ al-Ghaib by Fakhruddin Ar-Rāzī - Muhammad Fiqri Widhy Utomo (Darul Yasin Al Sys, 2026)
This article examines Fakhruddin ar-Rāzī’s interpretation of the isti‘żān verses in QS. an-Nūr 27–29, with Mafātīḥ al-Ghaib as the primary source. The study focuses on three main aspects: the interpretive character of Mafātīḥ al-Ghaib, ar-Rāzī’s exegetical treatment of the isti‘żān verses, and the implications of this interpretation for the protection of privacy and individual honor. Using a bibliographical approach and thematic analysis, this article shows that ar-Rāzī does not understand isti‘żān merely as a form of visiting etiquette, but as an ethical-legal framework that protects private space from disturbance, surveillance, and unauthorized entry. Mafātīḥ al-Ghaib demonstrates a distinctive integration of rational, linguistic, theological, and juridical interpretation, connecting the meaning of the verses to broader social structures. In ar-Rāzī’s interpretation, permission, greetings, body position, repeated requests for entry, the occupant’s right to refuse, and the prohibition of peeping constitute preventive mechanisms for safeguarding personal privacy, tranquility, dignity, and authority over private space. The study concludes that the central implication of ar-Rāzī’s interpretation of isti‘żān lies in its recognition of privacy as an inherent right of every individual, including within family relations and close social relationships. These findings contribute to Qur’anic studies by highlighting the relevance of classical exegesis to contemporary discussions on privacy, dignity, and ethical boundaries in social life.